Global unleashing of transcription elongation waves in response to genotoxic stress restricts somatic mutation rate - Matthieu D. Lavigne (Nature Portfolio, 2017)
Precise orchestration of gene expression regulation upon DNA damage is essential for genome integrity. Here the authors identify a novel widespread stress-triggered defence mechanism that promotes rapid transcription-driven genomic surveillance thus limiting mutagenesis and shaping cancer genomes.